Amerika - Amerikas Zur Geschichte eines Namens von 1507 bis zur Gegenwart - Lehmkuhl, Ursula; Rinke, Stefan (Historamericana, 2022)
The baptism of America 500 years ago, the expansion of the horizon of knowledge and the change in meaning that the name has experienced since then are the focus of this volume. This work reflects the new cultural-historical approaches in dealing with the Americas from 1507 to the present.